Release of Long-Chain Fatty Acids and Zinc from Hot Trub to Wort - Kühbeck, Florian; Back, Werner; Krottenthaler, Martin (BrewingScience, 2006)
The addition of hot trub to the fermenting wort has often been reported to enhance fermentation performance, while on the other hand, some of its components and their degradation products are thought to be detrimental to the quality of the resulting beer. In order to gain more knowledge of a potential improvement of yeast supply by nutrients like long-chain fatty acids (C14-C18:3) and zinc, release (re-dissolution) trials were carried out by adding hot trub to wort, both derived from industrial production. Free long-chain fatty acids were released mainly as palmitic and linoleic acid in a total amount of 0.9 mg/L additional to the content of 1–2 mg/L usually found in cold worts, while the hot trub particles showed a total reservoir of fatty acids in the order of 4 mg/L, which may be further released during fermentation. Zinc was released at an average concentration of 0.14 mg/L solely due to hot trub addition, this being relevant for yeast nutrition. For both nutrients, the maximum release was observed after a contact time of 4 h, while an extended period of up to 7 days did not lead to a further release. An increase of ethanol concentration to 5 %v/v, and/or a decrease of pH value to 4.0 in order to simulate some of the changes occurring during fermentation, did not impact on the release of neither fatty acids nor zinc in wort. These trials confirm a high bio-availability of zinc and to a lower extend also of long-chain fatty acids, thus, hot trub addition may improve nutrient supply of yeast, particularly when dealing with deficient worts, which might be the reason for the increase of fermentation performance reported earlier.